2015
DOI: 10.1016/j.msea.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation cross-slip controlled creep in Zircaloy-4 at high stresses

Abstract: a b s t r a c tUniaxial creep tests were performed on Zircaloy-4 sheet in the temperature range of 500-600 1C at high stresses ( 410 À 3 E), to uncover the rate-controlling mechanism. A stress exponent of 9.3-11 and a stressdependent activation energy in the range of 220-242 kJ/mol were obtained from the steady state creep data. TEM analyses revealed an extensive presence of hexagonal screw dislocation network on the basal planes indicating recovery of screw dislocations by cross-slip to be the dominant mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…experimental and simulated minimum creep rate as a function of stress (between 5 and 150 Mpa and temperature between 500 and 600°C) [56,57], (c), irradiation growth strain in the principal direction vs. dose, and (d) simulated strain rate vs. time curves for multiple creep stress obtained by varying solid solution H content, from 60 to 180 ppm. ...........21 Figure 22.…”
Section: List Of Figuresmentioning
confidence: 99%
“…experimental and simulated minimum creep rate as a function of stress (between 5 and 150 Mpa and temperature between 500 and 600°C) [56,57], (c), irradiation growth strain in the principal direction vs. dose, and (d) simulated strain rate vs. time curves for multiple creep stress obtained by varying solid solution H content, from 60 to 180 ppm. ...........21 Figure 22.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The creep strain behavior then can be rationalized from the unit processes that closely correlate to the energy barriers. Such an approach is extensively used for describing thermal creep in materials, especially for metals [19][20][21].…”
Section: Rate-theoretic Approach For Irradiation Creepmentioning
confidence: 99%
“…At higher stresses, the stress exponent changes to 3, approximately, followed by an even higher stress exponent. A stress exponent of 3 typically indicates a deformation mechanism through dislocation glide in metals; higher values of stress exponent indicate a crossover to a dislocation climb and cross-slip mechanisms [20].…”
Section: Rate-theoretic Approach For Irradiation Creepmentioning
confidence: 99%
“…While the jog density is very low at higher temperatures, fully formed subgrain boundaries have been detected by Murty (2015a, 2015b), consisting of pure edge dislocations and the special 'honeycomb' wall structure. The 'honeycomb' boundary, also recognized as Frank network (Hayes et al, 2002;Poirier, 1976), is reported in Kombaiah and Murty (2015a) as a 2-D structure on the basal plane. According to Murty (2015a, 2015b), its formation starts with the interaction between the screw dislocations on different prismatic planes, followed by cross-slip.…”
Section: Introductionmentioning
confidence: 99%